The Effect of Cognition Training on The Concentration of Low Intellectual Athletes in Open-Skill Sports - Alfian Faris Zulfiqar; Komarudin Komarudin; Mochamad Yamin Saputra; Geraldi Novian (Universitas Riau, 2024)
This research discusses the effect of cognitive training (life kinetik and brain gym) on the concentration of low-intellectual athletes in open-skill sports. This research was conducted to determine the effect of cognitive training (life kinetik and brain gym) on the concentration of low-intellectual athletes in open- skill sports and to determine the differences in influence between the two. This research is using experimental method. The population is 48 athletes in open-skill sports. The sample consisted of 27 athletes taken using purposive sampling technique. The instruments used in this research were Advanced Progressive Matrices (APM) and Concentration Grid Test (CGT). The data analysis technique used is the paired sample t-test and the independent sample t-test. The results of the research showed that there was a significant influence between life kinetik training and brain gym training on the concentration of low intellectual athletes in open-skill sports, but there was no significant difference in the influence between life kinetik training and brain gym training on the concentration of low intellectual athletes in sports. open skill sports.